The Application of Biologically Active Components Derived from Mineral, Synthetic, Phyto- and Organic Sources for Developing Local Hemostatic Agents: Historical Traditions and Contemporary Advancements - S. Abramov; S. Sokolovskyi; A. Gozhenko; I. Sobko; G. Titov; V. Gladyshev; M. Khmil; Ugis Kletnieks (Journal of Education, Health and Sport)
The present paper aims to provide an overview of the use of biologically active components derived from mineral, synthetic, phyto-, and organic sources in the development of local hemostatic agents. The study highlights the historical and contemporary use of these agents in medical practice, and examines the scientific evidence supporting their efficacy.